INDONESIAN ISLAMIC STOCK INDEX: MACROECONOMIC IMPACT - Hilmiatus Sahla (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study is to ascertain how the Indonesian Sharia Stock Index is impacted by macroeconomic factors such as interest rates, inflation, and exchange rates. The study sample for the Indonesian Sharia Stock Index's Annual Report for the years 2016 through 2020. The multiple linear regression analysis approach was used to test the data. According to the study's findings, the Indonesian Sharia Stock Index is influenced by the exchange rate variable to a lesser extent than previously thought, as seen by the significant values of 0.012 0.05 and tcount (-2.063) ttable (-2.00247), The results of a significant value of 0.288 0.05 and a tcount value of 1.072 ttable 2.00247 indicate that the inflation variable has no significant impact on the index of Indonesian Sharia shares, and the results of a significant value of 0.768 0.05 and a tcount value of 0.297 ttable 2.00247 indicate that the interest rate variable has no significant impact on the index of Indonesian Sharia stocks. The simultaneous values of Fcount = 5,693 Ftable 2.77 and Sig. F = 0.002 0.05. So, it can be inferred that the Indonesian Sharia Stock Index is significantly impacted by the fluctuating exchange rate, inflation, and interest rates. The coefficient of determination, or adjusted R square, is 0.193. According to this finding, exchange rates, inflation, and interest rates alone can account for 19.3% of the volatility in the Indonesian Sharia Stock Index, while other factors account for 80.7% of the variation.